Intracranial arachnoid cysts: Clinical study with the findings of 32 surgically treated cases - Isik, Nejat; Candan, Fatma; Başaran, Recep; Kuru, Lütfü İhsan; Isik, Nihal (Journal of Pediatric Neuroradiology, 2012)
Arachnoid cysts (ACs) are commonly encountered fluid collections in the central nervous system. Most cranial ACs are found incidentally and can be managed conservatively. This review presents and discusses clinical findings, diagnostic methods and management of intracranial ACs in 32 patients who were surgically treated in our clinic. The study included 23 male and nine female patients. Most of them were pediatric cases (77%) at the time of surgery. All diagnoses were confirmed on neuroradological examination. Twenty-six of the cysts were supratentorial (81.2%). The most common symptoms at presentation were seizures (50%), headache (37.5%), weakness (23%), and hydrocephalus (9%). Cystoperitoneal shunt placement, craniotomy, or endoscopic fenestration, are the surgical methods. Long-term outcome was favorable in most of these patients. Untreated, ACs may cause permanent severe neurological damage due to the progressive expansion of the cyst or hemorrhage. However, with surgical treatment most individuals with ACs do well.
Keywords: Arachnoid cyst; cranial; epilepsy; surgery